An NGS-Based Phylogeny of Orthotricheae (Orthotrichaceae, Bryophyta) With the Proposal of the New Genus Rehubryum From Zealandia - Draper, Isabel; Villaverde, Tamara; Garilleti, Ricardo; Burleigh, J. Gordon; McDaniel, Stuart F.; Mazimpaka, Vicente; Calleja, Juan A.; Lara, Francisco (Frontiers in Plant Science, 2022)
Phylogenomic data increase the possibilities of resolving the evolutionary and systematic relationships among taxa. This is especially valuable in groups with few and homoplasious morphological characters, in which systematic and taxonomical delimitations have been traditionally difficult. Such is the case of several lineages within Bryophyta, like Orthotrichaceae, the second most diverse family of mosses. Members of tribe Orthotricheae are common in temperate and cold regions, as well as in high tropical mountains. In extratropical areas, they represent one of the main components of epiphytic communities, both in dry and oceanic or hyper-oceanic conditions. The epiphytic environment is considered a hostile one for plants development, mainly due to its low capacity of moisture retention. Thus, the diversification of the Orthotrichaceae in this environment could be seen as striking. Over the last two decades, great taxonomic and systematic progress has led to a rearrangement at the generic level in this tribe, providing a new framework to link environment to patterns of diversification. Here, we use nuclear loci targeted with the GoFlag 408 enrichment probe set to generate a well-sampled phylogeny with well-supported suprageneric taxa and increasing the phylogenetic resolution within the two recognized subtribes. Specifically, we show that several genera with Ulota-like morphology jointly constitute an independent lineage. Within this lineage, the recently described Atlantichella from Macaronesia and Western Europe appears as the sister group of Ulota bellii from Zealandia. This latter species is here segregated in the new genus Rehubryum. The analysis of the ecological and biogeographical affinities of the species within the phylogenetic framework suggests that niche adaptation (including climate and substrate) could be a key evolutionary driver that shaped the high diversification of Orthotricheae.